APLIKASI PUPUK ORGANIK CAIR URINE KAMBING TERHADAP PERTUMBUHAN DAN HASIL MENTIMUN : APLIKASI PUPUK ORGANIK CAIR URINE KAMBING TERHADAP PERTUMBUHAN DAN HASIL MENTIMUN - Rizky Septika Utami; Eko Fransisko; Caca Handika (Pusat riset dan Inovasi Nasional, 2022)
Liquid organic fertilizer from goat urine is a fertilizer that dissolves easily in the soil and carries important elements for soil fertility. Fertilizers an important role in increasing crop yields, especially in soils with low nutrient content. The aim of the study was to obtain the optimum dose of goat urine liquid organic fertilizer for cucumber growth and to obtain the optimum dose of goat urine liquid organic fertilizer for cucumber yield. This study used a completely randomized design method and the treatment was goat urine liquid organic fertilizer (POC) consisting of 5 treatments, namely 0 ml/liter water, 50 ml/liter water, 100 ml/liter water, 150 ml/liter water, and 200 ml/liter of water. The administration of goat urine liquid organic fertilizer at a concentration of 200 ml/liter of water affected the cucumber growth variables, namely plant height, number of leaves, flowering age, and harvest age. Administration of goat urine liquid organic fertilizer at a concentration of 200 ml/liter of water affected the yield variables of cucumbers, namely number of fruit, fruit weight per fruit, fruit diameter, and fruit length.